2017
DOI: 10.1002/2016jg003576
|View full text |Cite
|
Sign up to set email alerts
|

Fluxes all of the time? A primer on the temporal representativeness of FLUXNET

Abstract: FLUXNET, the global network of eddy covariance flux towers, provides the largest synthesized data set of CO2, H2O, and energy fluxes. To achieve the ultimate goal of providing flux information “everywhere and all of the time,” studies have attempted to address the representativeness issue, i.e., whether measurements taken in a set of given locations and measurement periods can be extrapolated to a space‐ and time‐explicit extent (e.g., terrestrial globe, 1982–2013 climatological baseline). This study focuses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 72 publications
(158 reference statements)
1
105
0
Order By: Relevance
“…While it is well known that CO 2 concentration and budget estimates depend on the temporal coverage of sampling (Morales‐Pineda et al, ; Natchimuthu et al, ), we here show that this is also true for evaluations of environmental drivers of lake CO 2 . Our data confirms recent insights from terrestrial carbon flux studies (Chu et al, ; Montagnani et al, ) and highlights a general problem in empirical sciences: The scale of observed patterns and underlying mechanisms must match if observations are used to understand and predict patterns and processes (Levin, ).…”
Section: Discussionsupporting
confidence: 88%
“…While it is well known that CO 2 concentration and budget estimates depend on the temporal coverage of sampling (Morales‐Pineda et al, ; Natchimuthu et al, ), we here show that this is also true for evaluations of environmental drivers of lake CO 2 . Our data confirms recent insights from terrestrial carbon flux studies (Chu et al, ; Montagnani et al, ) and highlights a general problem in empirical sciences: The scale of observed patterns and underlying mechanisms must match if observations are used to understand and predict patterns and processes (Levin, ).…”
Section: Discussionsupporting
confidence: 88%
“…The emergence of shared eddy‐covariance (EC) ET a observations during the past few years (e.g., FLUXNET; Baldocchi et al, ) has substantially advanced our knowledge of terrestrial evapotranspiration in various ecosystems. Unfortunately, however, the observation period of most EC flux towers is shorter than a decade, thus impeding the depiction of long‐term variability in ET a (see Figure 1 in Chu et al, , for a detailed list of observational periods of the FLUXNET towers). Furthermore, the spatial distribution of the EC flux stations is uneven globally, with the majority of the stations operated in Europe and North America, having far fewer stations in Asia, South America, and Africa (Chu et al, ; Jung et al, ; Yu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, however, the observation period of most EC flux towers is shorter than a decade, thus impeding the depiction of long‐term variability in ET a (see Figure 1 in Chu et al, , for a detailed list of observational periods of the FLUXNET towers). Furthermore, the spatial distribution of the EC flux stations is uneven globally, with the majority of the stations operated in Europe and North America, having far fewer stations in Asia, South America, and Africa (Chu et al, ; Jung et al, ; Yu et al, ). Due to these difficulties, especially in developing countries, a need arises to develop robust estimates of large‐scale terrestrial evapotranspiration rates for a better understanding of land‐atmosphere energy and water exchanges at the regional, continental, and/or global scales and also to detect variations in diverse components of the hydrological cycle due to the ongoing climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Ecosystems do not generate water, but they modify the quantity, quality, and timing of water cycles. Global measurements of carbon and water fluxes using the eddy covariance method (Baldocchi et al 2001;Chu et al 2017) in recent decades clearly show that ecosystem primary productivity and ecosystem respiration are closely coupled with evapotranspiration processes (Sun et al 2011b). At the leaf level, plant stomata play a critical role in regulating both water and CO 2 fluxes in ecosystems.…”
Section: Carbon Cycle and Ecosystem Productivitymentioning
confidence: 99%